1995
DOI: 10.1128/jb.177.2.312-319.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genetic analysis of the neuD and neuB genes in region 2 of the polysialic acid gene cluster of Escherichia coli K1

Abstract: The K1 capsular polysaccharide, a polymer of sialic acid, is an important virulence determinant of extraintestinal pathogenic Escherichia coli. The genes responsible for the synthesis and expression of the polysialic acid capsule of E. coli K1 are located on the 17-kb kps gene cluster, which is functionally divided into three regions. Central region 2 encodes proteins necessary for the synthesis, activation, and polymerization of sialic acid, while flanking regions 1 and 3 are involved in polymer transport to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…E. coli K1 strain ATCC23511 neuD was amplified using primers 5Ј-cgtctagacgatgagtaaaaagttaataatatttggtgcggg-3Ј and 5Ј-cgggatcccgttcattccccctaattaatcttgttgg-3Ј based on published sequence (26) and cloned into pDCerm to produce pEcK1-NeuD. Sequencing of neuD from strain ATCC23511 revealed 99.5% identity with the published neuD sequence of E. coli K1 RS218 (NCBI accession number AAC43301), differing only at residue 164, where cysteine replaces valine.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli K1 strain ATCC23511 neuD was amplified using primers 5Ј-cgtctagacgatgagtaaaaagttaataatatttggtgcggg-3Ј and 5Ј-cgggatcccgttcattccccctaattaatcttgttgg-3Ј based on published sequence (26) and cloned into pDCerm to produce pEcK1-NeuD. Sequencing of neuD from strain ATCC23511 revealed 99.5% identity with the published neuD sequence of E. coli K1 RS218 (NCBI accession number AAC43301), differing only at residue 164, where cysteine replaces valine.…”
Section: Methodsmentioning
confidence: 99%
“…Using a separate approach, Tn916 mutagenesis, we defined the first gene of the biosynthetic operon (synX), showed that this gene was either the N-acetyl-D-glucosamine-6-phosphate 2-epimerase or the N-acetyl-D-mannosamine-6-phosphate phosphatase, demonstrated that a mutation in synX produced a capsule-defective (Cap ÏȘ ) phenotype, and clarified the nucleotide sequence of synB (45,47). Recently, Ganguli et al (18) reported the cloning and analysis of genes for group B polysialic acid biosynthesis in a third group B meningococcal strain and suggested, on the basis of amino acid homology with E. coli NeuB (1), that the protein encoded by synC (neuB) was the putative NANA synthetase. Edwards et al (10) later showed that a cloned copy of synC was capable of NANA synthesis in vitro.…”
mentioning
confidence: 99%
“…ORFs 1, 2, 3, and 4 shared, respectively, 59, 70, 51, and 60% identity to NnaD (NeuD), NnaB (NeuB), NnaC (NeuA), and NnaA (NeuC), encoded by the E. coli K1 capsule gene cluster (GenBank entries AAC43301, AAC43302, AAA24210, and AAA24211, respectively) (6). NnaA, NnaB, and NnaC of E. coli K1 synthesize CMP-Neu5Ac when they are cloned into E. coli K-12 on a plasmid (6), and NnaD has a role in the synthesis of CMPNeu5Ac by interacting with NnaB (17,18). NnaA is the GlcNAc 2-epimerase that converts GlcNAc to ManNAc.…”
mentioning
confidence: 99%